A Study of Alienation Representing Female Characters in Anita Desai’s Novels - Prem Bahadur Khadka (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article aims to draw the alienation theme in Anita Desai's novels. Desai's words illustrate the anxieties of the middle-class women involved in the family's isolation and alienation by making marital disharmony in their lives. Her novels correctly depict the exact notion that women need something more than food, clothes, and accommodation. Patriarchal culture is developed in the hands of Anita Desai through an encounter with the singularity of the Anglicized women of Indian society. She is one of the Indian writers who tried to change contemporary society's clichés with her pen.